2022
DOI: 10.32479/ijeep.13171
|View full text |Cite
|
Sign up to set email alerts
|

Effect of COVID-19 Pandemic on NSE Nifty Energy Index

Abstract: The research intends to assess the efficiency of NSE Energy Index-listed firms throughout the COVID-19 before and post pandemic phases, which run from 2019 to 2021. The primary goal of this article was to examine the price movement of corporations in the petroleum, gas, and electricity sectors by employing statistical methods such as descriptive statistics, ADF, and the GARCH (1,1) model, during the period of study. When comparing the post-COVID-19 pandemic era to the pre-COVID-19 pandemic period, certain firm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 6 publications
0
1
0
Order By: Relevance
“…This is not surprising given the history of favorable treatment of SOEs in China. Babu et al (2022) focused on the impact of COVID-19 on stock prices of India's publicly traded energy companies. They showed that in some enterprises, volatility remained at a much higher level during the COVID-19 pandemic relative to the time before the pandemic.…”
Section: Literature Reviewmentioning
confidence: 99%
“…This is not surprising given the history of favorable treatment of SOEs in China. Babu et al (2022) focused on the impact of COVID-19 on stock prices of India's publicly traded energy companies. They showed that in some enterprises, volatility remained at a much higher level during the COVID-19 pandemic relative to the time before the pandemic.…”
Section: Literature Reviewmentioning
confidence: 99%